2021
DOI: 10.1016/j.enfcli.2020.12.009
|View full text |Cite
|
Sign up to set email alerts
|

Association between sitting time and high-sensitivity C-reactive protein level among obese women

Abstract: Please check your proof carefully and mark all corrections at the appropriate place in the proof (e.g., by using on-screen annotation in the PDF file) or compile them in a separate list. Note: if you opt to annotate the file with software other than Adobe Reader then please also highlight the appropriate place in the PDF file. To ensure fast publication of your paper please return your corrections within 48 hours.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 14 publications
0
1
0
Order By: Relevance
“…In our study, women who sat the longest showed lower serum hs-CRP levels when they had the highest dietary fiber intake, as opposed to when they had the lowest dietary fiber intake. In the US, sitting for more than 4 h a day has been linked to increased BMI and obesity, contributing to elevated hs-CRP levels [ 90 ]. Another US cross-sectional study observed a 35–41% risk reduction in all-cause deaths and a 32–61% risk reduction in cardiovascular deaths when sitting for <6 h a day combined with high dietary fiber and vitamin intake [ 91 ].…”
Section: Discussionmentioning
confidence: 99%
“…In our study, women who sat the longest showed lower serum hs-CRP levels when they had the highest dietary fiber intake, as opposed to when they had the lowest dietary fiber intake. In the US, sitting for more than 4 h a day has been linked to increased BMI and obesity, contributing to elevated hs-CRP levels [ 90 ]. Another US cross-sectional study observed a 35–41% risk reduction in all-cause deaths and a 32–61% risk reduction in cardiovascular deaths when sitting for <6 h a day combined with high dietary fiber and vitamin intake [ 91 ].…”
Section: Discussionmentioning
confidence: 99%